2011
DOI: 10.1007/s00484-011-0462-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of repeated mild cold water immersions on the adaptation of the vasomotor responses

Abstract: There are several types of cold adaptation based on the alteration of thermoregulatory response. It has been thought that the temperature of repeated cold exposures during the adaptation period is one of the factors affecting the type of cold adaptation developed. This study tested the hypothesis that repeated mild cold immersions would induce an insulative cold adaptation but would not alter the metabolic response. Seven healthy male participants were immersed to their xiphoid process level repeatedly in 26°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 27 publications
0
23
0
1
Order By: Relevance
“…We set 23, 26, and 34 °C water temperature as severe cold, mild cold, and thermoneutral condition, respectively. The 23 °C condition was cold enough to induce shivering, but in 26 °C, no significant shivering was observed as shown in the previous report [12]. At least 1 week before the first test, participants were accustomed to perform one leg knee extension exercise using a specially designed device (Fig.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…We set 23, 26, and 34 °C water temperature as severe cold, mild cold, and thermoneutral condition, respectively. The 23 °C condition was cold enough to induce shivering, but in 26 °C, no significant shivering was observed as shown in the previous report [12]. At least 1 week before the first test, participants were accustomed to perform one leg knee extension exercise using a specially designed device (Fig.…”
Section: Methodsmentioning
confidence: 89%
“…The seasonal difference [5, 6], populations living in different climate [79], or people who work in cold work place [10, 11] have been studied for evaluating the cold acclimatization to the natural cold climate. On the other hand, cold acclimation studies have tested the change in physiological responses following a repeated cold exposure in a laboratory, mostly in resting condition [12, 13]. However, since human would have never acclimatized to cold alone without any physical activity, it is necessary to conduct a research assessing comprehensive effect of the physical activities in cold environment.…”
Section: Introductionmentioning
confidence: 99%
“…When exposed to cold environments, the human body will respond with vasoconstriction to decrease core and skin temperatures, so as to reduce heat loss from core to periphery by convection, and heat loss form periphery to environment by radiation and convection. Previous studies showed that human skin and peripheral vasoconstriction were enhanced after repeated exposures to cold water (Jansky et al., ; Wakabayashi et al., ; Young et al., ). In this study, skin temperature of the Shanghai group decreased more quickly than that of the Beijing group(see Figure ), suggesting greater vasoconstriction in the Shanghai group.…”
Section: Discussionmentioning
confidence: 95%
“…The wearing of bulky gloves to minimise the effects of tactile insensitivity may further impede dexterity. Again, cold adaptation plays an important role—cold adaptation of the hands can lead to diminished local vasoconstriction which allows increased circulation and skin temperatures in hands; this cold-induced vasodilatation is known colloquially as ‘fisherman's hand’ 33. Unfortunately, this response is not universal among subjects nor can it be trained by repeated cold exposure 34 35.…”
Section: Resultsmentioning
confidence: 99%